PROBLEMS AND CHALLENGES FACED BY SCHEDULED CASTE PEOPLE IN HARYANA -A CASE STUDY - Kumar, Dr.Satish; Pooja (Innovative Research Thoughts, 2018)
In India caste is a powerful organization. It provides a structure for arranging and organizing social groups in terms of their status and position in the social and economic system. This study addresses the problems and challenges faced by scheduled caste people in Haryana. In this study, primary data have used with the help of pre- structured questionnaire to 100 households during the year 2017.In this study, percentage method has used. Further, the results have interpreted with help of tabular analysis. The result based on quantitative and qualitative research revealed that the social and economic conditions of some respondents are not good. According to this study, the income sources of most families depend on labour sector. In labour sector, their income level is very low. Most of the people have less awareness about the government schemes and programmed. The suggestion given in the study can be cited to improve the conditions of scheduled caste in India.